2021
DOI: 10.3390/nano11020548
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Stability of LiNi0.5Mn1.5O4 by Coating with LiNbO3 Solid-State Electrolyte: Novel Chemically Activated Coating Process versus Sol-Gel Method

Abstract: LiNbO3-coated LiNi0.5Mn1.5O4 spinel was fabricated by two methods: using hydrogen-peroxide as activating agent and sol-gel method. The structure of the obtained cathode materials was investigated using a scanning electron microscope (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and the electrochemical properties of the prepared cathodes were probed by charge-discharge studies. The morphology of the coating material on the surface and the degree of coverage of the coated particles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…For the preparation of the cathodes, 0.9 g of NMC622 (BASF Toda, 90 wt %) or 0.9 g of Li­[Ni 0.5 Mn 1.5 O 4 ] (LNMO) (kindly provided by Binder, 90 wt %), 0.07 g of conductive carbon (Super P, Imerys, 7 wt %), and 0.03 g of binder (poly­(vinylidene fluoride) (PVdF) 1100, Kureha, 3 wt %) were weighed in a sample container and 2 mL of N -methyl-2-pyrrolidone (NMP) was added. The container was transferred to a Thinky centrifugal mixer and stirred twice for 5 min at 1700 rounds per minute.…”
Section: Methodsmentioning
confidence: 99%
“…For the preparation of the cathodes, 0.9 g of NMC622 (BASF Toda, 90 wt %) or 0.9 g of Li­[Ni 0.5 Mn 1.5 O 4 ] (LNMO) (kindly provided by Binder, 90 wt %), 0.07 g of conductive carbon (Super P, Imerys, 7 wt %), and 0.03 g of binder (poly­(vinylidene fluoride) (PVdF) 1100, Kureha, 3 wt %) were weighed in a sample container and 2 mL of N -methyl-2-pyrrolidone (NMP) was added. The container was transferred to a Thinky centrifugal mixer and stirred twice for 5 min at 1700 rounds per minute.…”
Section: Methodsmentioning
confidence: 99%
“…The initial step of the wet process method involves the dissolution of LNO precursors in a solvent. Mereacre et al [22] have shown that along with this solvent the addition of hydrogen peroxide might improve the LNO coating through surface activation [22]. Li et al [20] investigated the effect of LNO coating on nickel-rich NMC using a wet mixing method followed by heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…At normal conditions, the lowest temperature reported so far for obtaining crystalline LiNbO 3 is 400 °C . Recently, we have also reported the synthesis of LiNbO 3 from ethoxides and their use for the coating of LiNi 0.5 Mn 1.5 O 4 oxides . In this work, we used several different procedures for the synthesis of LiNbO 3 .…”
mentioning
confidence: 99%
“…In this work, we used several different procedures for the synthesis of LiNbO 3 . The first procedure was similar to an earlier-reported one and involved the reaction of lithium ethoxide and niobium ethoxide in a 1.15:1.00 mole ratio in absolute ethanol and H 2 O 2 (30%) at room temperature. As a result, a clear yellowish solution was produced.…”
mentioning
confidence: 99%
See 1 more Smart Citation